2020
DOI: 10.1017/s0007680520000288
|View full text |Cite
|
Sign up to set email alerts
|

Trade, Finance, and Industry in the Development of Indian Capitalism: The Case of Tata

Abstract: This article rethinks the relationship between trade and industry in the development of Indian capitalism, focusing on Tata, pioneers in textile and steel production. It shows how two little-known affiliated trading companies, R.D. Tata & Co. in Shanghai, Hong Kong, and Kobe, and Tata Limited in London, played a crucial intermediary role in securing financing and market access for the parent firm in Bombay while simultaneously increasing its exposure to the effects of global crises. Tata's ultimately domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has been found that the current regulation is not conducive to the liquidity of the stock market, and it is recommended that exposure to policy restrictions be exposed to attract new investors. Literature [7] rethought the trade-industry nexus in the process of capitalist development in India, starting with an in-depth analysis of the Tata Group, a giant in the textile and steel industries, focusing on how its overseas trading subsidiaries play a significant intermediary role in securing conditions in terms of financing and market access for the parent company, and Literature [8] investigated, based on the Clean Development Mechanism (CDM) of the Kyoto Protocol, the Mardushan, China Hydropower Station in the vicinity of the region, where the dam is financed with carbon financing, and based on the investigation found that the CDM consolidates hydropower governance and promotes a specific socio-economic modernization model in the western provinces of China. Literature [9] used the generalized matrix method to estimate the investment structure Q model on three aspects of financial development: financial depth, the degree of utilization of finance by state-owned enterprises and the degree of market-driven as well as the financing of commercial banks in the economy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the current regulation is not conducive to the liquidity of the stock market, and it is recommended that exposure to policy restrictions be exposed to attract new investors. Literature [7] rethought the trade-industry nexus in the process of capitalist development in India, starting with an in-depth analysis of the Tata Group, a giant in the textile and steel industries, focusing on how its overseas trading subsidiaries play a significant intermediary role in securing conditions in terms of financing and market access for the parent company, and Literature [8] investigated, based on the Clean Development Mechanism (CDM) of the Kyoto Protocol, the Mardushan, China Hydropower Station in the vicinity of the region, where the dam is financed with carbon financing, and based on the investigation found that the CDM consolidates hydropower governance and promotes a specific socio-economic modernization model in the western provinces of China. Literature [9] used the generalized matrix method to estimate the investment structure Q model on three aspects of financial development: financial depth, the degree of utilization of finance by state-owned enterprises and the degree of market-driven as well as the financing of commercial banks in the economy.…”
Section: Introductionmentioning
confidence: 99%